The Economics of agricultural development old wine or renaissance? - Roumasset, James (Asian Journal of Agriculture and Development, 2010)
In the wake of renewed attention on agricultural development as a promising strategy for sustained poverty reduction, the paper discusses how and to what extent the field of agricultural development is ripe for renewed investment. It first presents an overview of the history of thought in the economics of agricultural development. In the 1950s and 1960s, development economics was distinctly modernist, implicity accepting a planning mentality. In the 60s, agricultural development thinking retained the planning mentality but turned the "squeeze agriculture" philosophy on its head. The 1970s was described as the "growth with equity" decade. During this period, it was natural to promote agricultural development linkages through subsidies and market interference in the name of integrated rural development. Then in the 1980s, agricultural development thinking became more outward-oriented and infused with public economics (WDR, 1982; Bautista, 1987; Krueger et al. 1992; Gardner 1996). The idea that agricultural development might be efficiently supported through subsidies and protectionism slowly withered away. The paper cites recent literature on agricultural development: the World Development Report (WDR), 2008, the first World Bank report on food and agriculture in 25 years (after WDR 1982) and the Handbook of Economic Development, Volume IV, and poses the question, "Do these volumes reflect a renaissance in the field of agricultural development or are they merely old wine in a new bottle?" While WDR 1982 was revolutionary in its ca;; for liberalization, the 2008 report returns to the 1970s interventionism. Many of the policy ideas in WDR 2008 (e.g., subsidy for farmer cooperatives, Microfinance, crop insurance, and land reform) can only be properly evaluated with optimization and equilibrium models that incorporate transaction costs and such models have not been formalized. One possible reason for the failure of WDR 2008 to embrace mainstream economic policy analysis is that the team of authors that drafted the WDR are predominantly agricultural economists. The paper avers that if the economics of agricultural development is to succeed in helping real-world agricultural development live up to its pro=poor growth potential, it must co-evolve with innovations in mainstream economics. It adds that: 1) the nature, causes, and consequences of trade policy should be extended to an understanding of economic fragmentation inside the country and policies that can facilitate the evolution of change of specialization; and 2) the economics of space, time, and quality should be employed to understand the consequences of parastatal food marking concerns. Further, the infusion of public economics into the economics of agricultural development, which thrived in the 1980s, has stagnated due to the lack of foundations in transactions costs dynamics and the coevolution of specialization and governance. This, the stage is set for young dynamic scholars to develop new tools of analysis to build the foundations of a public microeconomics of development.